(untitled) (Journal of the College of Basic Education, 2026)
The language and speech of the Arabs were accepted as spoken and transmitted from them by hearing. Linguists did not establish rules, grammar, and morphology from them until later, as the great interest was for the sake of recording and preserving the Holy Qur’an, which is first and foremost. Then the language was taken from them as they spoke throughout the ages, followed by investigation and tracing, and combining similar words with similar words in their language and tongue. What deviated from their similar words was considered irregular or heard. What the Arabs spoke was from the origin of their speech and the language of their people, which is considered eloquent. As for what is not from their speech, it either deviated from the norm or entered foreign into their language, so they Arabized it or left it as foreign.